Optimal reception of multiple phase shift keying and quadrature amplitude modulation signals with non-coherent processing of harmonic interference - G. V. Kulikov; T. T. Do; A. A. Lelyukh; V. D. Nguyen (Российский технологический журнал, 2023)
Objectives. Analysis of the reception noise immunity of multiple phase shift keying (M-PSK) and quadrature amplitude modulation (M-QAM) signals has demonstrated a significant reduction in the quality of reception of discrete information due to the presence of various types of non-fluctuating interference in a radio communication channel including targeted harmonic interference. Therefore, the development of algorithms for compensating the influence of such forms of interference is an urgent task. While various methods for combatting this kind of interference, these vary in terms of their effectiveness. The aim of the present work is to synthesize and analyze the optimal algorithm for the reception of M-PSK and M-QAM signals with incoherent processing of harmonic interference.Methods. Various statistical radio engineering and computer simulation methods were used in accordance with optimal signal reception theory.Results. Synthesis and analysis of the optimal algorithm for receiving M-PSK and M-QAM signals with incoherent processing of harmonic interference were carried out. In addition to calculating the correlation integrals in the receiver, it is necessary to form weight coefficients, whose value depends on the correlation of the interference oscillation (extracted from the received mixture) with a sample of the interference stored in the receiver. The dependences of the bit error probability on the signal-to-noise ratio, interference detuning, and inaccuracy in setting the frequency and level of the interference sample in the receiver were obtained. It is shown that the higher the gain in the noise immunity of reception, the greater the intensity of the harmonic interference.Conclusions. The synthesized receiver circuit effectively compensates for harmonic interference. However, the efficiency of its operation depends on the detuning of the harmonic interference relative to the center frequency of the spectrum of the useful signal. The scheme for incoherent processing of harmonic interference remains operational even with small (within ±10%) inaccuracies in setting the frequency and the level of the interference copy in the receiver.